Exploring the Connection between Social Media Marketing Activities and Purchase Decisions, Focusing on Electronic Word of Mouth and Brand Awareness - Muhammad Aqib Shafiq; Muhammad Sajjad Khan; Salman Mehmood; Zia Ur Rehman (International Journal of Experiential Learning & Case Studies)
This paper examines the inspiration of social media marketing activities on customers’ purchase decisions in Pakistan. Following the development of a theoretical model comprising the prevalent activities undertaken in social media marketing – namely, trendiness, customization, and personalization – an online survey entailing 396 completed questionnaires was initiated to test its feasibility using the structural equation model. The analysis confirms the positive impact of SMMAs on purchase decisions, with a mediating role of electronic word of mouth and brand awareness. Moreover, brand image is found positively moderating the influence of electronic word of mouth on purchase decisions. This investigation is set to support online customers in their purchase decisions, along with helping companies in boosting electronic word of mouth and brand awareness using social media marketing activities.